Sejarah Tradisi Turun Mandi Di Nagari Sungai Nanam. Kabupaten Solok - Egi Gianturi; Dina Darmi Silfia (UIN Imam Bonjol Padang, 2023)
As a tradition of the bolawins Minangkabau people that has existed for a long time, this tradition of taking a bath still exists today. There have been many traditions of the Minangkabau people that have become extinct and have been abandoned by many people in Minangkabau. Some of the factors that make this tradition eroded by time include advances in technology, education, and the economy. However, there are also traditions that still persist and exist today, because these traditions can be adapted to the times and technological advances. Of the various traditions that still exist today, namely the tradition of showering, this tradition has been around for a long time and is still around today. Because this tradition can be adjusted to the current situation so that it is not eroded by the times. This tradition of taking a bath has several purposes, including as an expression of gratitude for the grace and gift from Allah SWT to humans who have been given offspring as the continuation of life in this world, then as a gathering between people starting from the bai's family with the baby's father's family, and also as a symbol in preserving the culture that has been left behind by previous ancestors so that these traditions are not extinct by the times. However, at the present time the tradition of taking a bath has been modified a lot depending on social conditions, economics, education, religion, and technology. The tradition of taking a bath in each region varies depending on the geographic conditions of the region.